2006
DOI: 10.1111/j.1742-7843.2006.pto_188.x
|View full text |Cite
|
Sign up to set email alerts
|

Trimidox Induces Apoptosis via Cytochrome c Release in NALM‐6 Human B Cell Leukaemia Cells

Abstract: Trimidox (3,4,5-trihydroxybenzamidoxime) has been shown to reduce the activity of ribonucleotide reductase accompanied by growth inhibition and the differentiation of mammalian cells. Here we examine the induction of apoptosis by trimidox in several human leukaemia cell lines, focusing on the release of cytochrome c and the activation of caspase proteases in the human B cell line NALM-6. Induction of apoptosis by trimidox (300 mM) was detected in NALM-6, HL-60 (premyelocytic leukaemia cells), MOLT-4 (an acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
1

Year Published

2007
2007
2008
2008

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…There was no effect until incubation with trimidox at 200 µM and slightly decreased cell survival at 300 µM (78.4 ± 5.6% of control), but it has no significant effect. This concentration had been shown to produce cell damage in several types of leukemia cells in our previous report (4). Incubation of the cells with a combination of trimidox (300 µM) and LPS (1 µg / ml) for 24 h had no significant effect on cell viability, as estimated by MTT assay (data not shown).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…There was no effect until incubation with trimidox at 200 µM and slightly decreased cell survival at 300 µM (78.4 ± 5.6% of control), but it has no significant effect. This concentration had been shown to produce cell damage in several types of leukemia cells in our previous report (4). Incubation of the cells with a combination of trimidox (300 µM) and LPS (1 µg / ml) for 24 h had no significant effect on cell viability, as estimated by MTT assay (data not shown).…”
mentioning
confidence: 64%
“…Trimidox (3,4,5-trihydroxybenzamidoxime) was shown to be one of the most potent in this series of compounds (3). Our lab has reported that trimidox induced apoptosis in human leukemia cell lines (4).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Trimidox (3,4,5-trihydroxybenzamidoxime) was shown to be one of the most potent in this series of compounds (5). Our lab has previously reported that trimidox induced apoptosis in a number of typical human leukemia cell lines, and the most susceptible cell was NALM-6, a B-cell line of acute lymphoblasyic leukemia, which expresses wild-type p53 (6). The aim of this study was to determine the contribution of p53 to trimidox-induced apoptosis.…”
mentioning
confidence: 96%
“…Apoptotic cells were estimated by nuclear morphological observation and DNA fragmentation analysis using our previous methods (6,10).…”
mentioning
confidence: 99%